1988
DOI: 10.1007/bf00640670
|View full text |Cite
|
Sign up to set email alerts
|

External load can alter the energy cost of prolonged exercise

Abstract: The present study was undertaken to examine the energy cost of prolonged walking while carrying a backpack load. Six trained subjects were tested while walking for 120 min on a treadmill at a speed of 1.25 m.s-1 and 5% elevation with a well fitted backpack load of 25 and 40 kg alternately. Carrying 40 kg elicited a significantly higher (p less than 0.01) energy cost than 25 kg. Furthermore, whereas carrying 25 kg resulted in a constant energy cost, 40 kg yielded a highly significant (p less than 0.05) increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 19 publications
1
42
1
Order By: Relevance
“…One study of 6 trained subjects who were asked to walk on a treadmill with 25-and 40-kg backpacks found that heavier loads resulted in increased energy costs over time. 19 Similarly, the exercise intolerance of overweight adolescents that we observed could be attributed to increased energy demands as a result of the extra load from excess adiposity. Our study demonstrated that the negative correlation between D12 and BMI was a continuous phenomenon: the greater the BMI, the more severe the functional impairment.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…One study of 6 trained subjects who were asked to walk on a treadmill with 25-and 40-kg backpacks found that heavier loads resulted in increased energy costs over time. 19 Similarly, the exercise intolerance of overweight adolescents that we observed could be attributed to increased energy demands as a result of the extra load from excess adiposity. Our study demonstrated that the negative correlation between D12 and BMI was a continuous phenomenon: the greater the BMI, the more severe the functional impairment.…”
mentioning
confidence: 51%
“…These studies have concluded that exercise intolerance in overweight children and adolescents is attributable primarily to the increased metabolic demands of carrying an excess load, rather than a true decrease in cardiorespi-ratory fitness. 15,[18][19][20] However, some studies have reported that overweight individuals have significantly decreased maximal heart rate; heart rate reserve, which is defined as maximal heart rate minus resting heart rate 15,16,21 ; and myocardial work efficiency. 22 Whether these differences significantly influence fitness and performance is unclear.…”
mentioning
confidence: 99%
“…In general, those changes have been shown to contribute to, or are at least suggestive of, an elevated energy cost of movement, an earlier onset of fatigue, and possibly an increased risk of injury (Epstein et al 1988;Knapik et al 2004). Morever, during deliberate mass placements away from the midline, those outcomes also show a lateral dependency, with an even greater postural disturbance and more rapid fatigue development (Park et al 2014).…”
Section: Load Carriage and Its Impact Upon Gaitmentioning
confidence: 99%
“…When subjects perform a loaded road march on a treadmill at a constant speed, exercise intensity increases over time if the load or speed is high enough (16,41). However, in the present study there was little change in exercise intensity (heart rate) in spite of large changes in march speed (Table 9) and environmental temperature.…”
Section: Performance Testsmentioning
confidence: 99%